Leisure constraints and the negotiation of structural relationships: a case study of scuba diving enthusiasts - Chen, Jing; Yu, Zihan; Ni, Ruiyang (Frontiers in Sports and Active Living, 2025)
BackgroundScuba diving has emerged as a popular recreational activity in China over the past two decades, yet academic research on this sport from the perspective of leisure studies remains limited. This study explores the relationship between leisure constraints and constraint negotiation among scuba diving enthusiasts, aiming to fill this research gap.MethodThis study employed a mixed-methods approach, combining in- depth interviews with 20 scuba diving enthusiasts and the Positive and Negative Affect Schedule (PANAS) for survey and analysis. The interviews focused on the participants' leisure motivations, the constraints encountered at different stages of their diving careers, and the negotiation strategies they employed.ResultsThe findings revealed that scuba diving enthusiasts tend to use cognitive negotiation strategies when addressing personal and interpersonal constraints, while predominantly employing behavioral negotiation strategies when dealing with structural constraints. A structural relationship was identified between leisure constraints and constraint negotiation, indicating that the type of constraint influences the negotiation strategy employed.ConclusionsThis study provides empirical support for the structural relationship between leisure constraints and constraint negotiation, enriching the materials available for leisure research. Future research is recommended to expand the sample size and further explore the underlying mechanisms of this relationship, as well as to consider the authenticity and accuracy of respondents' self-reports.